Relevansi Konsep Pendidikan Akhlak Ibnu Miskawaih Dan Ibnu Sahnun Dalam Konteks Pendidikan Kontemporer - Wahyuni, Riana; Dewi, Eva; Retnowari, Endang (Peneliti.net, 2025)
In addressing the complexities of contemporary educational challenges, comparing the concepts of moral education proposed by Ibn Miskawaih and Ibn Sahnun offers valuable insights. This study explores the relevance of these concepts in today's educational context. By analyzing their works, we can grasp the principles of ethics, morality, and character formation necessary in modern education. This comparison reveals both similarities and differences in their views on the goals of moral education, teaching methods, and the roles of teachers and students. The research also highlights the practical implications of their thoughts in formulating relevant and effective educational strategies amidst changing times. Thus, this study contributes to a deeper understanding of the comparison of moral education concepts according to Ibn Miskawaih and Ibn Sahnun, as well as the relevance of their concepts in contemporary education today